Colonoscopies in Australia - how much does the National Bowel Cancer Screening Program contribute to colonoscopy use? - Joachim Worthington; Emily He; Jie-Bin Lew; James St John; Christopher Horn; Paul Grogan; Karen Canfell; Eleonora Feletto (Sax Institute, 2023)
Objectives and importance of study: Colorectal cancer (CRC) is Australia's fourth most commonly diagnosed cancer. CRC screening is an effective intervention to reduce this burden. The National Bowel Cancer Screening Program (NBCSP) provides 2-yearly immunochemical faecal occult blood tests (iFOBTs) to Australians aged 50-74 years; a diagnostic colonoscopy is conducted after a positive iFOBT. Clinical guidelines inform colonoscopy usage, and appropriate use of these guidelines is vital to investigate gastrointestinal symptoms, detect bowel abnormalities and CRC, and remove precancerous polyps. Colonoscopy services are under strain, with limited formal strategies to prioritise patients. There are concerns among practitioners and patient advocates that the NBCSP generates additional colonoscopy requests and increases wait times, worsening patient outcomes and prolonging distress. In this research study, we estimate and project colonoscopy use in Australia from 2001 to 2030 and determine the impact of the NBCSP by examining model-estimated NBCSP colonoscopy demand. Methods: Colonoscopy use in Australia was compiled using Medicare Benefits Schedule (MBS) claims for colonoscopies from 2001 to 2019. From these data, projections were made from 2020 to 2030. Policy1-Bowel, a microsimulation model, was used to estimate NBCSP-related colonoscopy demand from screening follow-up and colonoscopic surveillance from 2006 to 2030. Results: MBS-funded colonoscopy use increased from 284 676 in 2001 to 663 213 in 2019. Annual use is projected to be more than 780 000 by 2030. Of these, 10-14% are projected to be generated by the NBCSP. Per-capita MBS-funded colonoscopy utilisation increased 0.2% annually over 2015-2019, a slowing of growth compared to previous trends. Conclusion: The NBCSP accounts for a modest fraction of colonoscopy use in Australia, and a better understanding of colonoscopy use not associated with the NBCSP is needed. Promoting adherence to guideline-recommended iFOBT and colonoscopy use could ease pressure on services and improve outcomes.